2019
DOI: 10.3897/natureconservation.34.30209
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biological and ecological long-term trends related to northern hemisphere climate in different marine ecosystems

Abstract: Data from five sites of the International Long Term Ecological Research (ILTER) network in the North-Eastern Pacific, Western Arctic Ocean, Northern Baltic Sea, South-Eastern North Sea and in the Western Mediterranean Sea were analyzed by dynamic factor analysis (DFA) to trace common multi-year trends in abundance and composition of phytoplankton, benthic fauna and temperate reef fish. Multiannual trends were related to climate and environmental variables to study interactions. Two common trends in biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 117 publications
0
16
0
Order By: Relevance
“…for the North Sea benthos, which was affected by low SST in the 1980s, resulting in reduced abundances of warm-temperate species, which further dropped in abundance after an exceptionally cold winter in 1995/1996 [60][61][62]. After a biological and climate regime shift in 2000/ 2001, several studies observed a general increase in species number [43,63,64] with a consecutive increase in warmtemperate species and decrease in cold-temperate species at various trophic levels of the marine ecosystem and provided evidence on possible further climate-related shifts around 2010 [65]. By contrast, the faunal communities of other systems (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…for the North Sea benthos, which was affected by low SST in the 1980s, resulting in reduced abundances of warm-temperate species, which further dropped in abundance after an exceptionally cold winter in 1995/1996 [60][61][62]. After a biological and climate regime shift in 2000/ 2001, several studies observed a general increase in species number [43,63,64] with a consecutive increase in warmtemperate species and decrease in cold-temperate species at various trophic levels of the marine ecosystem and provided evidence on possible further climate-related shifts around 2010 [65]. By contrast, the faunal communities of other systems (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The third phase started with shifts around 2010–2016. While this phase is too recent to indicate a consistent ecosystem shift, plankton communities in five marine LTER ecosystems (Kröncke et al, 2019) and hypolimnetic dissolved oxygen in five of six Canadian lakes (Nelligan et al, 2019) showed a regime shift around 2010. During the third phase, a possible decrease in DO in the upper layers was observed above that explained by temperature‐dependent oxygen solubility.…”
Section: Discussionmentioning
confidence: 99%
“…Around 2010/11 single studies indicated drastic changes in the marine ecosystem [43, 89, 104]. Wernberg et al [43] found a regime shift in a tropical environment after a marine heat wave in around 2011.…”
Section: Discussionmentioning
confidence: 99%